Community Empowerment Through Healthy Food Processing Training and Sports Health as an Effort to Prevent SEZ and Stunting in Nagari Maek, Bukik Barisan District, Lima Puluh Kota Regency - Anggun Permata sari; Yogi Andria; Pudia M Indika (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
The nutritional problem that often occurs in the Nagari Maek community is a lack of nutrient intake which will lead to malnutrition, chronic energy deficiency (KEK), stunting, lack of protein energy and anemia. The prevalence rate for children with chronic energy deficiency and stunting in Nagari Maek is still relatively high. Chronic lack of energy and stunting in toddlers will continue until the child grows up, if no improvement is made. Cases of chronic energy deficiency and stunting that occur in childhood are risk factors for increased mortality, low cognitive abilities and motor development and imbalanced body functions. Significant cognitive impairment will cause a decrease in children's learning outcomes when they enter school age. The results of this activity concluded 1) Increased knowledge and understanding of healthy food processing, 2) Increased knowledge and understanding of sports health, 3) Increased knowledge and understanding of prevention of SEZ and stunting from an early age.